2012
DOI: 10.1111/j.1600-0404.2012.01669.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-frequency rTMS on motor neuron excitability after stroke

Abstract: Low-frequency rTMS applied to the non-lesional hemisphere might be potentially useful therapeutically for post-stroke patients with spastic upper limb hemiparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…Mally et al [17] reported that repeated application of 1 Hz RTMS to the nonlesional hemisphere for one week significantly reduced spasticity of the affected upper limb in poststroke patients. Similarly, our group reported previously that 20-min application of LF-RTMS over the nonlesional hemisphere decreased F-wave amplitude in the affected upper limb in poststroke patients, without any significant effect on motor neuron excitability in the unaffected upper limb [18]. With regard to intensive OT, Kagawa et al [19] investigated the effect of constraint-induced movement therapy on motor neuron excitability in the affected upper limb using F-wave measurement.…”
Section: Discussionmentioning
confidence: 93%
“…Mally et al [17] reported that repeated application of 1 Hz RTMS to the nonlesional hemisphere for one week significantly reduced spasticity of the affected upper limb in poststroke patients. Similarly, our group reported previously that 20-min application of LF-RTMS over the nonlesional hemisphere decreased F-wave amplitude in the affected upper limb in poststroke patients, without any significant effect on motor neuron excitability in the unaffected upper limb [18]. With regard to intensive OT, Kagawa et al [19] investigated the effect of constraint-induced movement therapy on motor neuron excitability in the affected upper limb using F-wave measurement.…”
Section: Discussionmentioning
confidence: 93%
“…These electromagnetic signal pulses varied from 0.3 to 30 Hertz (cycles per second). Device-generated pulsed electromagnetic fields (PEMF) have been effective for bone stimulation, stroke rehabilitation, decreased postoperative pain, and other applications (Abo et al, 2012; Heden & Pilla, 2008; Kondo et al, 2013). Transcutaneous electrical nerve stimulation (TENS) units are a well-known example of an adjustable pulsed electromagnetic field that is used to decrease chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Mally & Dinya (24) showed that multiple sessions of 1-Hz rTMS using a circular coil significantly reduced the spasticity of affected limbs in chronic stroke patients. Kondo et al (25) reported that a single session of 1-Hz rTMS significantly decreased the F/M ratio in affected upper limbs. Reducing spasticity after rTMS in stroke patients might thus depend on the stimulated area or the duration and frequency of rTMS.…”
Section: Discussionmentioning
confidence: 99%